Logic Probability and Criminal Evidence in Chile: ¿Influence of Common Law Culture? - Vera Sánchez, Juan Sebastián (2021)
This work will refer to the reception by Chilean doctrine and cases law of the logical probability from Anglo-Saxon evidence in criminal matters. I will try to justify that this has occurred from the interpretation of theprinciple of sufficient reason as a logical limit from sound criticism concept and I will also expose some difficulties detected.This research is intended to be a contribution to the dialogue between the legal cultures of the common law and civil law systems. This work also seeks to delve into a certain historical perspective of the evolution of the studies of criminal evidence in the Ibero-American criminal procedural systems, because it is necessary to generate links of communications between the perspectives of Anglo-Saxon evidence and continental procedural law to promote rationality and justice of adjudications in matters of the facts. The first part of this work will refer to logical probability in the context of the new evidence scholarship. The second part will refer to the proof of the facts in the civil law tradition, from the Enlightenment to the present day. The third part will refer to logical probability in Chilean doctrine and case law. The last part will discuss a possible reception of the concept of logical probability in criminal evidence in Chile.